Differential transcript and soluble factor patterns in macrophage/enterocyte-like monolayer co-cultures based on apical or basolateral LPS exposure - Mazzei, Aurora; Cucchiara, Martina; Mortara, Lorenzo; Bossi, Elena; Schiavone, Roberta; Verri, Tiziano; Bruno, Antonino; Barca, Amilcare (Frontiers in Immunology, 2025)
BackgroundThe monolayer of intestinal epithelial cells (IECs) plays a crucial role in controlling intestinal homeostasis, also by its interaction with the immune system, via paracrine cytokine production, thus driving innate responses by tissue-resident immune cells. Here, using a co-culture model, we investigated the interactions between differentiated Caco-2 cells in monolayer and macrophages, by mimicking the cross-talk between enterocytes and immune cells during gastrointestinal (GI) tract inflammation.MethodsCaco-2 mature monolayers grown on Transwell membranes were challenged with apical or basolateral LPS. After stimulations, the enterocyte-like monolayers were transferred in co-culture with THP-1 derived macrophages. The functional impact of treatments was evaluated in terms of monolayer’s permeability, expression of mRNAs related to inflammation and immune responses and analysis of immune soluble factors present in the co-culture media.ResultsLPS effectively affected monolayer’s permeability and induced a pro-inflammatory transcriptional program in Caco-2 monolayers. Remarkably, THP-1 derived macrophages differentially responded based on the diverse directional source of LPS, previously administered to the Caco-2 monolayers. Basolateral sensing of LPS, by Caco-2 monolayers, induced specific increase of several pro-inflammatory factors such as NF-kB1, IL-6 and IL-8, at transcript level, in macrophages, while apical sensing triggering targeted increase of IL-1β expression. Significantly, the analysis of immune factors secreted in the co-culture media suggested that paracrine interactions between enterocyte-like monolayers and macrophages are differently driven based on the basolateral vs. apical inflammation, previously triggered by LPS against the epithelial monolayer, and thus involving different immune gene networks.ConclusionsTaken together, our results suggest a framework of interactions between IECs and macrophages, depending upon the “polarized” inflammatory dysregulation.